Orofaciodigital syndrome type IV (Mohr-Majewski syndrome) with severe expression expanding the known spectrum of anomalies. - Meinecke, P (1990)
We present a male infant with hypertelorism, median pseudo-cleft of the upper lip and cleft palate, lobulated tongue, hypoplastic larynx and epiglottis, mesomelic shortening of limbs with particularly short and broad tibiae, polydactyly of the upper limbs, severely hypoplastic external genitalia with anorchidism, anal atresia, severe congenital heart defect, and renal agenesis. These features show considerable overlap with severe Majewski type short rib-polydactyly syndrome and so expand the known spectrum of anomalies in orofaciodigital syndrome type IV.